2019
DOI: 10.3390/sports7010023
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Stair Climbing as an Exercise Routine among Healthy Older Adults Attending a Community-Based Physical Activity Program

Abstract: Stair climbing provides a feasible opportunity for increasing physical activity (PA) in daily living. The purpose of this study was to examine the daily walking and stair-climbing steps among healthy older adults (age: 74.0 ± 4.9 years; Body Mass Index (BMI): 22.3 ± 2.5 kg/m2). Participants (34 females and 15 males) attended a weekly 6-month community-based PA program. During the entire program period, daily walking and stair-climbing steps were recorded using a pedometer (Omron, HJA-403C, Kyoto, Japan). Befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…With regards to body composition characteristics, this study results suggest that trainee older, change this factor after 8-weeks concurrent strength and aerobic training. This outcomes show a BMI decrease as expected due to different studies show a lower BMI level in older people as much activity they do [64] other authors agree but in a six month climbing stairs protocol in sedentary people [20] that it is less intensity but longer; in all cases exist no significant differences.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…With regards to body composition characteristics, this study results suggest that trainee older, change this factor after 8-weeks concurrent strength and aerobic training. This outcomes show a BMI decrease as expected due to different studies show a lower BMI level in older people as much activity they do [64] other authors agree but in a six month climbing stairs protocol in sedentary people [20] that it is less intensity but longer; in all cases exist no significant differences.…”
Section: Discussionsupporting
confidence: 78%
“…These changes cause a body composition improvement at both functional and performance levels [17,18]. Better body composition is normally associated with regular PE, thereby previous research observed differences in body composition between PE trained older women and non-trained older women [5,[19][20][21]. There even exist differences between active and inactive older women in body composition [22,23].…”
Section: Introductionmentioning
confidence: 97%
“…To date, we have knowledge about the health benefits of stair climbing [10][11][12][13]. However, no data exist about participation and performance trends in tower running, and especially about the sex difference in this specific running discipline.…”
Section: Introductionmentioning
confidence: 99%
“…The recent literature abounds in studies on the health-enhancing effects of stair climbing. Muscle strength and endurance improved after a training program that included stair-climbing (Hongu et al, 2019). Stair climbing in naturalistic settings improved energy levels in all participants with males also showing improved cognitive performance (Stenling et al, 2019).…”
Section: Introductionmentioning
confidence: 93%
“…Prompts to use stairs at worksites show mixed results with negative effects (Åvitsland et al, 2017), positive effects (Bellicha et al, 2016) and with most studies showing increased stair climbing during intervention (Soler, 2010). Training programs may result in increased stair-climbing when feelings of self-efficacy are enhanced (Hongu et al, 2019), or where short-term benefits from stair-climbing are emphasized, rather than longer term health benefits (Allais et al, 2017). Improving the visibility of the stairway alternative, using only visual information, results in 6% increase in the up-flow and 7% in the down-flow (Van Calster et al, 2017).…”
Section: Introductionmentioning
confidence: 99%